From Panic and Neglect to Investing in Health Security : Financing Pandemic Preparedness at a National Level - International Working Group on Financing Preparedness (World Bank, Washington, DC, 2017)
Deadly infectious pandemics will mark humanity's future, as they have shaped its past. Neither individual governments nor the global community can entirely prevent the emergence of infectious threats. But we can be much better prepared. This report by the International Working Group on Financing Preparedness (IWG) proposes ways in which national governments and development partners can finance investments in country and regional preparedness and response capacities for pandemics and other health emergencies. Preparedness for pandemics refers to health and non-health interventions, capabilities, and capacities at community, country, regional, and global levels. Their purpose is to prevent, detect, contain and respond to the spread of disease and other hazards, mitigating social disruptions and limiting risks to international travel and trade.